All Equal in Death? Fighting inequality in the contemporary funeral industry. Issue 9 (September 2018) - Audebrand, Luc K.; Barros, Marcos
This paper examines how alternative economic organizations can fight inequality without help from traditional partners such as social movement organizations. We focus on co-operatives' successful battle against corporate dominance in the Québec funeral industry. We analyse their actions through the lens of Nancy Fraser's tridimensional theory of justice, which utilizes the cultural dimension of recognition, political dimension of representation, and economic dimension of distribution. We demonstrate how funeral co-ops empowered their federation to influence institutional inequality while maintaining a co-op identity by embodying the potentially contradictory flexibility of social movements along with co-op principles. This paper contributes to scholarship on collective social action by exploring the dual role of model and movement played by secondary co-ops such as the federation of Québec funeral co-ops, which draws on local institutional and organizational resources to disrupt unfair structures. We also extend Fraser's theory, using it as a framework for understanding the dynamic relationships between inequality and its potential remedies at different levels of analysis.